SEXUAL HARASSMENT ON WOMEN JOURNALISTS IN INDONESIA - Shafa Alfariza Putri Puspita (Cahaya Ilmu Bangsa, 2024)
There has been a lot of research on sexual harassment experienced by women. owever, this is not the case withresearch on sexual harassment against female journalists. Women who work as journalists are one of the vulnerable groups in cases of sexual harassment. Even though journalism itself is a profession tasked with reporting the truth to the public, many cases of violence against female journalists have not been revealed. This research was conducted to obtain data about the forms of sexual harassment that occur, patterns of perpetrators, and the impact of events. The method used is a qualitative method with an exploratory type. Data collection techniques were carried out through interviews andfocus group discussions. From the results of the interviews, information was obtained that the four informants experienced verbal harassment which led to physical harassment. From the perspective of the perpetrator, the three victims said that the perpetrator of the sexual harassment was the source they wanted to interview, while another informant said that the perpetrator of the sexual harassment was his superior at the office. In terms of impact, the four informants said that they experienced trauma, although it did not last long. The four informants also stated that they chose not to pursue their cases in the legal arena.